Analisis Perbandingan Pengalaman Pengguna Pada Aplikasi Dompet Digital (Studi Kasus Pada OVO dan DANA) - Ahmad Nur Hidayat; Buce Trias Hanggara; Bonda Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Smartphone users in Indonesia are increasing every year so that many application development companies have created application-based non-cash payment services to make it easier for users to make non-cash payments. Many digital wallet applications have sprung up, including the Ovo and Dana application. The purpose of this research is to compare 2 digital wallet applications that have almost the same business processes and characteristics in the experience of using the two digital wallet applications. This study provides a comparison of user experience analysis based on scenario testing with parameters of time per completed task, error during task performance, number of clicks during task completion and task success rate as well as user experiance questionnaire (UEQ) parameters which have six aspects of assessment, including attractiveness, perspicuity, efficiency, dependability, stimulation and novelty. Scenario testing was carried out on 10 respondents who had never previously used these two applications and the UEQ questionnaire was distributed to 20 respondents. The results of the test assignment or scenario show that the respondent's success is quite high even though the previous respondent has never used these two applications. Funding applications have a higher value in two parameters, namely the error during task performance and number of clicks during task completion and the Ovo application is better in the time per completed task parameter and the task success rate parameter aspects of both applications have the same good value. The results of the UEQ questionnaire show that respondents have a positive tendency towards the two digital wallet applications where the fund application has a better value in four aspects of the measurement scale, namely attractiveness, perspicuity, dependability and novelty. Meanwhile, the ovo application has a better value in terms of efficiency and stimulation.